HPLC first approach in detecting thalassemia and other common hemoglobinopathies is more cost and time effective - Periyavan, Sundar; Kumar, Sudha; Mamatha, G. N.; Hegde, Santhosh; Jain, Suman; Dhanya, Rakesh; Agarwal, Rajat Kumar; Faulkner, Lawrence (Frontiers in Hematology, 2025)
IntroductionThis study aimed to study the effectiveness of high-performance liquid chromatography (HPLC) as the initial step for thalassemia/hemoglobinopathy carrier identification in contrast to the conventional complete blood count (CBC)-first approach.Materials and methodsThis multicenter study was conducted in four hospitals in South and Central India from July 2021 to December 2022, enrolling 6,549 antenatal women. Complete blood count and HPLC tests for the beta-thalassemia trait and common variants were performed. Cost-effectiveness and efficacy of three different approaches: CBC as the first step followed by HPLC for low mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) samples, HPLC as the first step, and HPLC and CBC performed together.ResultsThe sensitivity and specificity of the first step with MCV and MCH cut-offs for all hemoglobinopathy carriers were 80.8% and 50% respectively. For beta-thalassemia carriers alone, the sensitivity and specificity were 96.1% and 50.6%. For sickle cell disease carriers, the sensitivity was 69% while the specificity was 51.4%. If using only CBC as the first step, we would have missed 14.1% of all hemoglobinopathy carriers. The cost of conducting HPLC first was 0.7% higher than conducting CBC as the first step and then following up with HPLC. The increase in cost was 47.8% if we performed HPLC and CBC together.ConclusionWe conclude that conducting HPLC as the first step is cost-effective, saves time and labor, and seems to be the preferable approach for prevention programs. HPLC as the first step identified several types of hemoglobinopathies, including alpha and beta variants, that would have otherwise been missed by the conventional CBC-first screening method.